Evaluation of oral health and malocclusion among blind children and teenagers in Mazandaran in 2019 - Pedram Abedi; maysam mirzaee; Sahba Amini; Mohammad Mehdi Naghibi Sistani (Tehran University of Medical Sciences, 2021)
Background and Aims: Information collection about the malocclusion and oral health in blind children is essential to plan for their education in schools. Therefore, this study aimed to evaluate the status of malocclusion and oral health among blind children and teenagers in Mazandaran, Iran. Materials and Methods: The population of this included 150 blind children and teenagers aged from 10 to 18 years who were referred to the public and private centers cities including Sari, Babol, Freydoonkenar, and Babolsar in Mazandaran, Iran in 2019. Information on maxillary occlusion status, oral hygiene index, and DMFT index was extracted through clinical examination. Data were analyzed using SPSS23 software by ANOVA and Chi-square tests in addition to the descriptive statistics. Results: The mean DMFT was 10.25 (SD 4.67). Oral hygiene status was good in 16% of participants, moderate in 82%, and poor in 2%. There was no significant difference between girls and boys in terms of oral hygiene status (P=0.5). In all cases, 35.8% had class I malocclusion, 29.8% had class II malocclusion, and 14.6% had class III malocclusion. Class II malocclusion was more common in girls and class I in boys (P=0.01). Conclusion: Dental caries and occlusal abnormalities were common among blind children and adolescents living in Mazandaran province. Addressing the oral and dental needs of the blind should be a priority for health policymakers in this province in Iran.